2010
DOI: 10.3109/14767058.2010.494745
|View full text |Cite
|
Sign up to set email alerts
|

Pouch function and gastrointestinal complications during pregnancy after ileal pouch-anal anastomosis

Abstract: Pregnancy after IPAA is overall safe, associated with limited complications and no significant alteration in pouch function. Vaginal delivery appears as safe as cesarean section for most women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Several studies of women who underwent IPAA found no increased rates of adverse pregnancy outcomes 189 and no change in pouch function after vaginal delivery. [189][190][191][192][193][194] One survey reported that 17% of women had some degree of permanent deterioration of pouch function after delivery, but this was not related to method of delivery. 195 Although several studies of pregnancies after IPAA have shown vaginal delivery to be as safe as cesarean delivery in terms of pouch function, 193,194,196 physiological measurements and imaging studies suggest that there is a higher risk of sphincter injury with vaginal than cesarean delivery.…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies of women who underwent IPAA found no increased rates of adverse pregnancy outcomes 189 and no change in pouch function after vaginal delivery. [189][190][191][192][193][194] One survey reported that 17% of women had some degree of permanent deterioration of pouch function after delivery, but this was not related to method of delivery. 195 Although several studies of pregnancies after IPAA have shown vaginal delivery to be as safe as cesarean delivery in terms of pouch function, 193,194,196 physiological measurements and imaging studies suggest that there is a higher risk of sphincter injury with vaginal than cesarean delivery.…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 99%
“…196 Data on the risk of fecal incontinence in pregnant women with IPAA are conflicting. 193,195,197 One study reported that women with IPAA had increased stool frequency and fecal incontinence during pregnancy, 195 whereas others found no association during 193 or after pregnancy. 197 A cohort study found that rates of incontinence were not significantly affected by mode of delivery.…”
Section: Medical Management Of Ibd During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Small bowel obstruction is a rare complication in women with an IPAA after cesarean delivery. 86,100,101…”
Section: Postoperative Carementioning
confidence: 99%
“…Several studies, however, have yielded conflicting results regarding these outcomes 14, 17-20 . The presence of active perianal disease is also of concern in vaginal delivery, as a vaginal trauma or laceration at the time of delivery may hypothetically lead to progressive perianal symptoms or non-healing fistula in a patient with active perianal CD.…”
Section: Introductionmentioning
confidence: 99%